1996
DOI: 10.1007/s002040050353
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of vitamin E on chromium (VI)-induced cytotoxicity and lipid peroxidation in primary cultures of rat Hepatocytes

Abstract: Pretreatment of primary cultures of rat hepatocytes with alpha-tocopherol succinate (vitamin E) for 20 h prior to exposure to K2Cr2O7 resulted in a marked decrease of chromium (VI)-induced cytotoxicity, as evaluated by the leakage of lactate dehydrogenase, without affecting cellular uptake and the subcellular distribution of chromium. The levels of chromium (VI)-induced lipid peroxidation, as monitored by malondialdehyde formation, were also inhibited by pretreatment with the vitamin. Pretreatment with vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 25 publications
5
26
1
1
Order By: Relevance
“…The present study also showed that chromium (VI) treatment resulted in decreased levels of nonenzymatic antioxidants such as GSH, vitamins C and E, and inhibited activities of enzymatic antioxidants such as GR, GSH-Px and SOD in cultured rat hepatocytes. Similar results were observed in previous studies [40][41][42]. In the present study, pretreatment with DDTC had no effect on the reduction of GSH or vitamin C level or on inhibition of GR, GSH-Px or SOD activity induced by chromium (VI).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study also showed that chromium (VI) treatment resulted in decreased levels of nonenzymatic antioxidants such as GSH, vitamins C and E, and inhibited activities of enzymatic antioxidants such as GR, GSH-Px and SOD in cultured rat hepatocytes. Similar results were observed in previous studies [40][41][42]. In the present study, pretreatment with DDTC had no effect on the reduction of GSH or vitamin C level or on inhibition of GR, GSH-Px or SOD activity induced by chromium (VI).…”
Section: Discussionsupporting
confidence: 93%
“…Concerning these antioxidants, our previous studies with cultured hepatocytes also showed that a metal chelator DFO had no influence on cellular levels of GSH and the activities of GR as well as SOD, however this chelator attenuated the suppression of cellular levels of vitamin C and vitamin E induced by chromium (VI), resulting in the suppression of chromium (VI)-induced DNA breaks, cytotoxicity and lipid peroxidation [41]. Similarly, treatment with vitamin E or melatonin inhibited chromium (VI)-induced cytotoxicity as well as lipid peroxidation, and normalized the levels of vitamins C and E suppressed by dichromate, without affecting such antioxidant enzymes as GSH-Px, SOD and CAT [40,42]. These and the present study suggest that the protective effect of DDTC against chromium (VI)-induced cytotoxicity and lipid peroxidation may be related more to the levels of nonenzymatic antioxidants such as vitamin E than to the enzymatic antioxidant activity within cells.…”
Section: Discussionmentioning
confidence: 99%
“…These reactive intermediates are formed along with oxygen radicals generated via Fenton-like and other possible reactions that occur during intracellular reduction [9], which also intensively trigger the massive production of reactive oxygen species causing oxidative damage, protein cross-linkage, genomic instability and apoptosis, destruction of cellular protein, lipid and DNA [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although pretreatment of isolated rat hepatocytes with vitamin E or vitamin C protected the cells from chromium(VI)-induced lipid peroxidation , vitamin E had no effect on chromate-induced cytotoxicity . Moreover, pretreatment of primary cultures of rat hepatocytes with vitamin E (Susa et al, 1996) or deferoxamine (Susa et al, 1997) protected cells from both chromate-induced cytotoxicity and lipid peroxidation. In animals studies, it has been shown that dietary pretreatment of rats or guinea pigs with vitamin E (Chorvatovicová et al, 1991) or vitamin C (Ginter et al, 1989;Chorvatovicová et al, 1991) protected bone marrow cells from chromium(VI)-induced cytoxicity.…”
Section: Introductionmentioning
confidence: 97%
“…The role of physiological antioxidants, namely vitamin E and vitamin C, as well as the role of the membrane-permeable metal-chelating agent deferoxamine in chromium(VI)-induced cellular injury, including cytotoxicity, and lipid peroxidation has been studied in mammalian cells and experimental animals (Sugiyama, 1992;Susa et al, 1996Susa et al, , 1997. It has been shown that pretreatment of cultured Chinese hamster V-79 cells with vitamin E protected cells from chromate-induced cytotoxicity (Sugiyama et al, 1989).…”
Section: Introductionmentioning
confidence: 99%